2012
DOI: 10.1530/rep-11-0371
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed plasma microRNAs in premature ovarian failure patients and the potential regulatory function of mir-23a in granulosa cell apoptosis

Abstract: Recent studies implicate the regulatory function of microRNAs (miRNAs) in oocyte maturation and ovarian follicular development. Differentially expressed miRNAs are found in the plasma of premature ovarian failure (POF) patients and normal cycling women. In this study, miRNA-regulated signaling pathways and related genes were described using Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes pathway analysis. The effect of mir-23a on granulosa cell apoptosis was also studied by examining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 48 publications
8
125
0
9
Order By: Relevance
“…In addition, the clinical relevance of miRNAs has steadily grown over the past few years particularly in relation to their significant potential as biomarkers of tissue function (Laterza et al 2009, Schwarzenbach et al 2011. Also, the possibility that miRNAs associated with certain clinical diseases, including ovarian diseases (Yang et al 2012), could be therapeutically targeted has generated enormous interest within medical communities (Pfeifer & Lehmann 2010). An increased understanding of ovarian miRNAs over the coming years will facilitate the application of this potential in clinical reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the clinical relevance of miRNAs has steadily grown over the past few years particularly in relation to their significant potential as biomarkers of tissue function (Laterza et al 2009, Schwarzenbach et al 2011. Also, the possibility that miRNAs associated with certain clinical diseases, including ovarian diseases (Yang et al 2012), could be therapeutically targeted has generated enormous interest within medical communities (Pfeifer & Lehmann 2010). An increased understanding of ovarian miRNAs over the coming years will facilitate the application of this potential in clinical reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al (2012) reported attenuation of activininduced proliferation of mouse granulosa cells by miR-145 targeting of both activin receptor 1B and cyclin D2. In another study, Yang et al (2012) showed that miR-23a was pro-apoptotic in cultured human luteinised granulosa cells presumably by decreasing the levels of X-linked inhibitor of apoptosis protein (XIAP) and increasing caspase-3 cleavage, although it was not clarified whether these were actually direct targets of miR-23a in granulosa cells. Finally, using a microarray approach in porcine ovarian follicles, Lin et al (2012) found that miR-26b expression increased during follicular atresia and further showed that this miRNA could induce granulosa cell death by directly targeting ataxia telangiectasia mutated (ATM), a gene involved in DNA repair.…”
Section: Involvement Of Mirnas During Follicular Growth and Steroidogmentioning
confidence: 99%
“…Several studies have already reported effects of specific miRNAs on different aspects of granulosa cell function , including steroidogenesis (Yao et al 2010, Xu et al 2011, Yin et al 2012, Dai et al 2013, proliferation (Yao et al 2010, Yan et al 2012, Dai et al 2013, survival (Carletti et al 2010, Yang et al 2012, terminal differentiation (Kitahara et al 2013), and cumulus expansion (Yao et al 2014). With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other analyses using exome sequencing, in a family with nine affected women [75], and in a consanguineous Middle-Eastern family with five affected women [76,77], have suggested new candidate genes (Table 4). Moreover, recent studies relate the regulatory function of microRNAs (miRNAs) in oocyte maturation and folliculogenesis, and different miRNA expression profiles in the plasma of POI patients and fertile women have been detected when a miRNA microarray analysis was performed [78]. Similar results have been observed in an animal model in which a different profile for differentially expressed miRNAs has been observed between normal rats and 4-vinylcyclohexene diepoxide (VCD)-induced rat POF when miRNA microarrays were used [79].…”
Section: Novel Candidate Poi Genes Identified By Genome-wide Analysismentioning
confidence: 59%